Deformation mechanisms in Ti/TiN multilayer under compressive loading. (1st January 2017) - Yang, Wei; Ayoub, Georges; Salehinia, Iman; Mansoor, Bilal; Zbib, Hussein
Abstract: The promising mechanical, physical and chemical properties of nano-scale metal/ceramic multilayers (MCMs) are of high interest for extreme environment applications. Understanding the plastic deformation mechanisms and the variables affecting those properties is therefore essential. The interface characteristics and the plastic deformation mechanisms under compressive loading in a Ti/TiN multilayer with a semi-coherent interface are numerically investigated. The interface structure of the Ti/TiN interface and the interface misfit dislocation were characterized using molecular dynamic simulations combined with atomically informed Frank-Bilby method. Three possible atomic stacking interface structures are identified according to the crystallographic analysis of the interface. Upon relaxation, large interface areas are occupied with the energetically stable configuration. Furthermore, the higher energy stacking are transformed into misfit dislocations or dislocation nodes. The molecular dynamic compressive stress strain response of the Ti/TiN multilayers exhibited three distinctive peaks. The first peak was generated by the dislocation dissociation of perfect dislocation into pairs of partials dislocation around extended nodes region at the interface. Upon further compression the second peak, identified as the first yielding, resulted from the activation of pyramidal slip planes in the Ti layer. Finally, a third peak identified as the second yielding, occurred when dislocation nucleated/transmitted in/into the TiN layer. Graphical abstract: Image 1